Autonomous Mobile Wheelchair Powered Via EOG Signal Recognition - Wan Daud, Wan Mohd Bukhari; Bohari, Zul Hasrizal; Sulaima, Mohamad Fani; Jali, Mohd Hafiz (IEEE Xplore, 2014)
The approach of the wheelchair control by using electrooculography (EOG) signal recognition is proposed in this paper. This method allows users to control their wheelchair by using eyes movement. The main objective of this project is to identify the hyperpolarization and depolarization existing between retina and cornea that produce the corneal-retinal potential (CPR). The amplitude of CRP is collected from 5 participants while the results in form of signal are transferred to the Matlab environment for analyzed. The signal analysis was carried out to attain some information about the signals such as maximum and minimum value. Threshold level is determined based on the features of the signal and it has been used to determine the direction of the wheelchair. The implementation of the threshold level set using the CRP collected onto the wheelchair prototype is successfully achieved.